(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The access to real-time and updated data, in particular information about the position of firms and their competitors in the market, has become the top priority of organizations worldwide. The dynamic and rapidly changing business environment and the increasingly intensive competition suggest that companies require ongoing monitoring of the market, the behaviour and preferences of their customers and their competitors. Frequently updated information enables the firm to proactively, rather than reactively, act towards its competitors and clientele. The paper proposes and analyzes various methodologies and frameworks that employ the mobile labour of firms (such as technicians and maintenance personnel) for gathering information on the premises of clients and their surrounding neighbourhood. As mobile workers already gain access to the client and insights about the product or the service provided by their firm, they can broaden the scope of information gathered from her. The data streams continuously provided by mobile workers require IT infrastructure for transferring, structuring and processing this information to enrich managers and strategic decision makers within the firm with up-to-date, real world insights. The study presents the methodology and proposes different IT architectures that can support the implementation of mobile intelligence gathering in a variety of organizations. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.